The Monument of Heroic Events and Students’ Historical Imagination in Padang - Yefterson, Ridho Bayu; Syafrina, Yelda; Lionar, Uun (Paramita: Historical Studies Journal, 2023)
Nowadays, history teachers are challenged to present exciting and meaningful history learning for students. To achieve that, being a creative teacher is a demand and a challenge for history teachers must do. This study aims to explain the use of historical relics in the form of monuments as sources and media for learning history. This study uses a qualitative approach, with data collection techniques, namely, field observations on the historical menu, interviews with history teachers, and literature studies on relevant historical works. The findings of this study indicate that the City of Padang has many historical monuments applicable to history learning materials. The monument was built to commemorate important events around the independence revolution in Padang, which teachers still need to optimize as sources and media for learning history. Monuments can be used as sources and media for education history, which aims to provide students with a better understanding and description of the events of the revolution and teach students to interact directly with historical sources. Collingwood’s approach to the importance of imagination in historical reconstruction can be adopted in the learning process. The teacher can develop students’ historical imagination by creating a learning atmosphere that makes monuments and monuments the object of their imagination of historical events. Thus, students are expected to appreciate better the fighters’ struggle in the war in Padang to defend independence. In addition, students are also likely to assess inspiration and values that can be used as motivation and role models in the life of the nation and state.Keywords: Monument, independence revolution, historical imaginationSaat ini, guru sejarah memiliki tantangan untuk menghadirkan pembelajaran sejarah yang menarik sekaligus bermakna bagi para siswa. Kreativitas guru menjadi tuntutan dan tantangan yang harus yang mesti dipenuhi oleh guru sejarah. Penelitian ini bertujuan untuk menjelaskan bagaimana benda peninggalan sejarah berupa monumen dapat dimanfaatkan sebagai sumber dan media pembelajaran sejarah. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan kunjungan lapangan, wawancara, dan studi pustaka terhadap karya-karya sejarah yang relevan. Temuan dari penelitian ini menunjukkan bahwa Kota Padang memiliki banyak monumen bersejarah. Monumen tersebut dibangun untuk mengenang peristiwa-peristiwa penting sekitar revolusi kemerdekaan di Kota Padang yang selama ini belum dioptimalkan oleh guru sebagai sumber dan media belajar sejarah. Monumen dapat dijadikan sebagai sumber dan media pembelajaran sejarah yang bertujuan untuk memberikan pemahaman dan gambaran yang lebih baik kepada siswa mengenai peristiwa revolusi. Imajinasi sejarah siswa dapat diciptakan dengan menghadirkan siswa langsung di tempat monumen tersebut berada kemudian dikolaborasikan dengan kemampuan guru dalam mendeskripsikan konteks dari peristiwa yang terjadi. Dengan demikian, siswa diharapkan dapat lebih mengapresiasi perjuangan para pejuang di Kota Padang serta membuat penilaian sendiri tentang inspirasi dan nilai yang bisa dijadikan motivasi dan role model dalam kehidupan berbangsa dan bernegara dalam perang kemerdekaan. Kata Kunci: Monumen, revolusi kemerdekaan, historical imagination